Environmental Change and Settlement at Tel Lachish, Israel - Rosen, Arlene M. (Bulletin of ASOR, 1986)
Alluvial sequences in central Israel reveal a history of climatic and landscape changes from Chalcolithic through Byzantine times. These are closely related to social and historical events at Tel Lachish. The deposits indicate a moister climate during initial settlement in the Chalcolithic period and Early Bronze Age. Rapid floodplain buildup in MB I suggests an instability in the drainage system corresponding to widespread abandonment of Levantine cities, including Lachish. A dry period of wadi incision followed. This lasted until a phase of colluvial deposition in the Late Iron Age, which apparently resulted from neglected agricultural terraces after the Assyrian destruction of Israelite Lachish. A later fill accompanied Byzantine settlement and may be related to an amelioration in climate.